2010
DOI: 10.1002/jso.21541
|View full text |Cite
|
Sign up to set email alerts
|

Case‐matched analysis of totally laparoscopic versus open liver resection for HCC: Short and middle term results

Abstract: Background and Objectives: Laparoscopy is gaining acceptance as a safe procedure for resection of liver neoplasms. The aim of this study is to evaluate surgical results and mid-term survival of minor hepatic resection performed for HCC. Methods: Data of 16 patients with HCC, undergoing laparoscopic hepatectomy from September 2005 to January 2009, were compared to a control group of 16 patients who underwent open resection (OR) during the same period. The two groups were matched in terms of type of resection, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
86
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(96 citation statements)
references
References 15 publications
8
86
2
Order By: Relevance
“…This extensive review of the literature in combination with our clinical experiences indicate that pure laparo- [34] NA NA NA NA NA NA 0/25 1/33 Aldrighetti et al [35] 0/16 1/16 NA NA 6.3 ± 1.7 9.0 ± 3.8 0/16 0/16 Tranchart et al [36] 3/42 11/42 0/36 4/53 6.7 ± 5.9 9.6 ± 3.4 1/42 1/42 Kim et al [37] of their operating time and blood loss was 288 min and 50 mL. From these experiences, we propose the following advantages of laparoscopic hepatectomy for HCC patients: (1) advantageous for repeat procedures: Repeat pure laparoscopic hepatectomy (and combined treatments) for patients with liver cirrhosis and multicentric/ metachronous HCCs was feasible and safe.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…This extensive review of the literature in combination with our clinical experiences indicate that pure laparo- [34] NA NA NA NA NA NA 0/25 1/33 Aldrighetti et al [35] 0/16 1/16 NA NA 6.3 ± 1.7 9.0 ± 3.8 0/16 0/16 Tranchart et al [36] 3/42 11/42 0/36 4/53 6.7 ± 5.9 9.6 ± 3.4 1/42 1/42 Kim et al [37] of their operating time and blood loss was 288 min and 50 mL. From these experiences, we propose the following advantages of laparoscopic hepatectomy for HCC patients: (1) advantageous for repeat procedures: Repeat pure laparoscopic hepatectomy (and combined treatments) for patients with liver cirrhosis and multicentric/ metachronous HCCs was feasible and safe.…”
Section: Introductionmentioning
confidence: 69%
“…The safety and feasibility of the laparoscopic approach and its short-term benefits for HCC patients with chronic liver dysfunction have been demonstrated by several series [21][22][23][24][25][26][27][28][29][30][31] . To date, several studies have investigated the major differences between laparoscopic hepatectomy and open hepatectomy (Tables 1 and 2) [32][33][34][35][36][37][38][39] . Favorable short-term results, including fewer incidences of ascites and liver failure, and shorter postoperative hospital stays, correlate with the laparoscopic procedure.…”
Section: Laparoscopic Hepatectomy For Hcc Patients: An Overviewmentioning
confidence: 99%
“…However, in selected patients who undergo surgery by experienced hands, one of the most important advantage of the laparoscopic approach is the potential improvement in terms of blood loss and transfusion rates [4][5][6][7][8][9][10][11]. This specific improvement of the laparoscopic approach in comparison to open surgery was particularly underlined by the experts at the Morioka consensus.…”
Section: Discussionmentioning
confidence: 99%
“…), bleeding control during laparoscopic liver resection (LLR) is a liverspecific improvement, which has been underlined by many experts [4][5][6][7][8][9][10][11]. Several studies aimed to elucidate the factors responsible for reduced blood loss during laparoscopic liver surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] While early experience was focused on benign diagnoses, this approach is now used for many hepatic malignancies. [7][8][9][10][11] It is accepted that minimally invasive liver resections have similar perioperative morbidity, mortality and long-term survival as open resections, 5,9 and some studies have shown that laparoscopic liver resection is associated with less blood loss, shorter hospital stay and comparable longterm survival. 12 However, the procedures are technically demand ing, and advanced skills in laparoscopy are required.…”
mentioning
confidence: 99%